Disease-miRNAdb: a manually-curated database for the investigation of the microRNA-human disease relationship - Shin, Jae Moon; Lim, Wooyoung; Lee, Kyung-Mi; Won, Jung Im; Jung, Da Woon; Nho, Chu Won; Kang, Kui Dong; Yoon, Jee Hee; Cho, Yoon Shin (SPRINGER, 2017)
MicroRNAs (miRNA) of approximately 22 nucleotides are fundamental molecules in cellular biology that act by modulating target gene expression. As a post-transcriptional/translational regulator, the role of miRNAs in human disease is highly expected. Recently, a rising number of miRNAs that are associated with a variety of human diseases have been reported in the literature. Aiming to provide a comprehensive of resource of miRNAs that are related to the human disease, we built the Disease miRNA Database (Disease-miRNAdb). MiRNAs from three groups of diseases including kidney disease, cancer, and metabolic disease were manually curated in the current version of database located on a user-friendly online website (http://disease-miRNAdb.hallym.ac.kr). In addition, this database also includes information regarding single nucleotide polymorphisms (SNPs) located in pre-miRNAs, miRNA flanking regions, and 3'-UTRs of miRNA target genes. The generation of genetic variation in these regions may result in a loss or gain of miRNA-target gene interactions, which may influence the development of disease. Thus, information regarding miRNA-related SNPs will be useful in the discovery of disease-associated miRNAs in human populations by employing SNP association analysis for the disease of interest. Disease-miRNAdb will be continually maintained with up-to-date information to provide a current and valuable resource for investigating the roles of miRNAs in human disease.
Keywords: ASSOCIATION